The incentives of employers' associations to raise rivals' costs in the presence of collective bargaining - Justus Haucap; Uwe Pauly; Christian Wey (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
This paper explores the role that employers' associations may play in centralized wage bargaining processes. It thereby adds to the literature on labor markets, in which the relationship between union behavior and unemployment has been explored quite extensively, while employers' associations have been almost escaped economic analysis so far. The paper shows that employers' associations may possibly foster a wage increase due to their potential incentives to raise rivals' costs. In a simple model, it is shown that employers' associations can use standard wages as a barrier to entry to product markets if producers differ in labor productivity. We identify conditions, under which unions will prefer entry deterring standard wages compared to a system of competitive wage determination, and the paper shows that there may be cases in which a centralized union acting in a wage revenue maximizing manner may actually prevent minimum wages from raising above certain levels. Depending on the exact parameter values unions may then offset the adverse effects employers' federations can have on the industry's employment rate. Starting from our formal model we argue that minimum wage legislation might actually be favored by employers' federations. Furthermore, we show that the German labor law provides for a mechanism to set minimum wages by the industry itself: Wage agreements between unions and employers' associations can be made legally binding for the entire industry through a so-called Allgemeinverbindlicherklärung. As a final example we analyze the incentives the West German employers' association had to implement high wages in Eastern Germany in order to avoid competition from laborinefficient, but low-wage East German firms. – – Diese Arbeit untersucht die Rolle von Arbeitgeberverbänden in zentralisierten Lohnverhandlungen. Der Beitrag ergänzt die existierende Literatur über Arbeitsmärkte, in der zwar die Beziehungen zwischen Gewerkschaftsverhalten und Arbeitslosigkeit ausgiebig analysiert werden, die Rolle der Arbeitgeberverbände jedoch fast durchweg im verborgenen bleibt. Die Arbeit zeigt, daß Arbeitgeberverbände unter Umständen bestrebt sind, Lohnerhöhungen durchzusetzen, um die Lohnkosten von nicht-organisierten Konkurrenzunternehmen überproportional zu erhöhen. In einem einfachen Modell wird bewiesen, daß ein Arbeitgeberverband Anreize hat, allgemein verbindliche Löhne als ein Instrument zur Errichtung von Markteintrittsbarrieren zu benutzen, wenn die nichtorganisierten Unternehmen eine niedrigere Arbeitsproduktivität aufweisen. Des weiteren wird die Rolle einer Gewerkschaft untersucht, die die Lohnsumme ihrer Mitglieder maximiert. Es werden die Parameterkonstellationen spezifiziert, so daß die Gewerkschaft einen Lohn präferiert, der unter dem marktzutrittsverhindernden Lohn liegt, den der Arbeitgeberverband durchsetzen möchte. Auf der Grundlage des Modells argumentieren wir, daß Arbeitgeberorganisationen unter Umständen für die Implementierung von Minimallöhnen eintreten. Als weitere Anwendungen des Modells diskutieren wir die Allgemeinverbindlicherklärung (AVE) von Tarifvereinbarungen in Deutschland und die Bereitschaft der westdeutschen Arbeitgeberverbände nach der Wiedervereinigung Deutschlands, die rasche Angleichung des ostdeutschen Lohnniveaus an das Westdeutschlands zu befürworten.
Keywords: 330